PENGARUH RASIO PROFITABILITAS, LEVERAGE, SIZE, DAN SALES GROWTH TERHADAP RETURN SAHAM YANG DIMEDIASI OLEH DIVIDEN (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Periode Tahun 2012-2014) - Pramana, Michael Sandra; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2016)
This study aims to analyze the effect of Return On Equity (ROE), Debt Equity Ratio (DER), size, and sales growth toward stock return with using Dividend Payout Ratio (DPR) as mediator variable, case study on manufacture company in Indonesian Stock Exchange during period 2012-2014. Reseacrh population used manufacture company in Indonesian Stock Exchange during period 2012-2014. Taken samples of the all purpose 30 companies by using purposive sampling method. The data used in this study were obtained from the Indonesian Capital Market Directory (ICMD) 2011-2015. IDX Company Report and www.idx.co.id. Analysis technique used Ordinary Least Square Regression (OLS), statictics t-test, sobel test, and classics assumption test that includes of normality test, multicollinearity test, heteroskedastisitas test, and autocorrelation test. The result shows that ROE has positive association with DPR, DER has negative association with DPR, size has positive association with DPR, sales growth hasn’t association with DPR, DPR has positive association with stock return, and the other variable hasn’t association with stock return. The result of path analysis and sobel test also showed that DPR may mediate the effect of ROE and size on stock return.